P27 inhibits CDK6/CCND1 complex formation resulting in cell cycle arrest and inhibition of cell proliferation. Issue 19 (18th October 2018) - Li, Niannian; Zeng, Jie; Sun, Fuze; Tong, Xiaoling; Meng, Gang; Wu, Chunman; Ding, Xin; Liu, Lanlan; Han, Minjin; Lu, Cheng; Dai, Fangyin
ABSTRACT: p27 plays critical roles in cell proliferation, differentiation, and apoptosis, which have been well studied in mammals and Drosophila . However, the mechanisms underlying p27 regulation of the cell cycle have not been thoroughly researched. In this study, Genevestigator, Kaplan–Meier Plotter, and the Human Protein Atlas databases were used to analyze the expression of p27, cell division protein kinase 6 (CDK6 ), and cyclin D1 ( CCND1), as well as its prognostic value in different tumor tissues and corresponding normal tissues. Quantitative PCR and immunohistochemistry were used to detect the expression of p27, CDK6, and CCND1 in the tissues of cancer patients. The effects of p27, CDK6, and CCND1 on the proliferation of lung cancer cells were examined by the MTT assay, and flow cytometry was used to investigate the mechanism by which p27 affected cell proliferation. Immunofluorescence, co-immunoprecipitation, and Western blotting were used to determine if p27 interacted with CDK and CCND1 to regulate the cell cycle. The results showed that p27, CDK6, and CCND1 played different roles in tumorigenesis and development, which are in accordance with CDK6 and CCND1 in affecting the cell cycle and cell proliferation. p27 regulated the cell cycle and inhibited cell proliferation by affecting formation of the cell cycle-dependent complex CDK6/CCND1, but did not directly affect the expression of CDK6 and CCND1 . Moreover, CCND1 did not regulate the cell cycle alone, but rather, functioned together with CDK6 . This study provides insights into the effects of p27 on tumor formation and development, and the underlying regulatory mechanisms.